Improved Creep Resistance at 1000°C of a Medium Entropy Alloy by the In Situ Formation of Intergranular MC Carbides - Gay, Corentin; Chenikha, Nassima; Spaeter, Pauline; Etienne, Erwan; Vernière, Anne; Aranda, Lionel; Berthod, Patrice (CV. Literasi Indonesia, 2024)
A Cantor’s alloy with modified contents in manganese and chromium, elaborated by classical foundry, was enriched either in tantalum and carbon or in hafnium and carbon, to promote the formation of MC carbides to try improving the poor creep resistance of the original quinary alloy for possible use at 1000°C. Similarly to what was observed in recent investigations, metallography allowed checking that interdendritic/intergranular MC carbides were obtained here too. The two monocarbides–containing alloys were first subjected to differential thermal analysis to specify notably their melting start temperatures, to validate the chosen temperature for the creep tests. Three-point flexural creep tests were then performed at 1000°C, which indisputably demonstrated the outstanding strengthening effect of these MC carbides for the modified Cantor’s alloy.